2019
DOI: 10.3390/ijms20235872
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Neuroprotective Effects of Panax ginseng G115® and Ginkgo biloba GK501® Combinations In Vitro Models of Excitotoxicity

Abstract: Neurological-related disorders are seen as an increasingly important aspect of welfare. While conventional medicine is still the mainstay for the treatment of these diseases, it is becoming apparent that patients are also seeking more natural and preventative interventions. Panax ginseng G115® and Ginkgo biloba GK501® extracts alone or in combination were used in two in vitro experimental models of primary cultures exposed to excitotoxicity: rat organotypic hippocampal slices exposed to either 5 µM kainic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…KA triggers a delayed type of excitotoxic cell death in the CA3 area of organotypic hippocampal slices through activation of ionotropic glutamate receptors [ 27 , 28 ]. Additionally, it has been shown that KA induces cell death through caspases activation [ 29 ], increase expression of pro-apoptotic proteins, such as Bim and Bax, which lead to a decrease in the Bcl-2-Bad ratio, paralleled release of cytochrome c and cleavage of poly(ADP-ribose)-polymerase (PARP) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…KA triggers a delayed type of excitotoxic cell death in the CA3 area of organotypic hippocampal slices through activation of ionotropic glutamate receptors [ 27 , 28 ]. Additionally, it has been shown that KA induces cell death through caspases activation [ 29 ], increase expression of pro-apoptotic proteins, such as Bim and Bax, which lead to a decrease in the Bcl-2-Bad ratio, paralleled release of cytochrome c and cleavage of poly(ADP-ribose)-polymerase (PARP) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The neuronal degeneration mediated by KA involves ER stress and the activation of ER sensors [ 45 ]. In organotypic hippocampal slices, KA induces a selective death in the CA3 region [ 27 , 28 , 46 ]. We observed that at a concentration of 10 or 20 µM, TQ was able to reduce neuronal damage induced by KA ( Figure 2 F).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Damage in the human corneal and conjunctival epithelial cells was quantitatively evaluated by measuring the amount of the soluble cytosolic enzyme LDH released from injured cells into the extracellular fluid, 5,10 and 15 min after exposure to the drugs, using the LDH kit, as previously described for mix cortical cells (Landucci et al, 2019).…”
Section: Evaluation Of Cell Death: Ldh Assaymentioning
confidence: 99%
“…Neuroprotective effects of natural compounds were confirmed by the study of Landucci and collaborators that suggested that both Panax ginseng and Ginkgo biloba extracts may mediate their effects by activating phosphorylation of ERK1/2 and Akt signaling pathways, so protecting against excitotoxicity-induced damage [ 10 ].…”
mentioning
confidence: 99%